Exploring Gender Dynamics Intersects with Educational Attainment in Rural and Urban Areas to Influence Access to Decent Work and Equal Pay in Punjab, Pakistan - Aleesha Abbas; Hashim Raza; Laraib khan; Rahat Raza; Alina Raza; Aqsa Nasarullah; Sultan Mahmood; Sadia Naz, (Dialogue Social Science Review (DSSR), 2025)
This study analyzes the intersections of gender, education, and rural dynamics in the pursuit of decent employment and equal pay in Punjab, Pakistan. It aims to understand how gender disparities in education, compounded by socio-cultural norms, influence employment opportunities and wage equality in both rural and urban settings. The research seeks to provide insights into the socio-economic factors that contribute to the determined issues faced by women in the workforce. A qualitative examine plan was active, including thorough meetings with 30 respondents from diverse socio-economic backgrounds across various districts of Punjab. Participants were carefully selected to represent a broad range of experiences and perspectives related to education, employment, and gender roles. Data collection was facilitated through a semi-structured interview guide, allowing for a comprehensive exploration of the key issues. Thematic analysis was utilized to systematically identify and analyze patterns within the data, linking these themes directly to the research objectives. Key findings reveal that women in rural areas face significant barriers to employment due to traditional gender roles, limited access to quality education, and socio-economic constraints. Urban women, while benefiting from better educational opportunities, still encounter challenges related to wage disparity and occupational segregation. These findings highlight the ongoing struggles women face in achieving economic equity in both rural and urban contexts. The study concludes with several pertinent recommendations, advocating for targeted educational reforms to improve access to quality education for women in rural areas, alongside awareness campaigns aimed at challenging entrenched gender norms. Furthermore, the study emphasizes the need for robust policy interventions to enforce equal pay legislation and create more inclusive work environments. These measures are essential to advancing gender equality and promoting economic empowerment in Punjab, Pakistan